Paul Martsching letter to Robert K. Myers regarding bird sightings, spring 1988 - Martsching, Paulet al (1988)
Field notes contributed by Paul Martsching in a letter to Robert K. Myers. The field notes include detailed descriptions of several birds. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed